Immediate and long-term relationship between severe maternal morbidity and health-related quality of life: A prospective double cohort comparison study - Aniza, Abd Aziz; Norhayati, Mohd Noor; Nik Hazlina, Nik Hussain (BioMed Central Ltd., 2016)
Background: Given the growing interest in severe maternal morbidity (SMM), the need to assess its effects on quality of life is pressing. The objective of this study was to compare the quality of life scores between women with and without SMM at 1-month and 6-month postpartum in Kelantan, Malaysia.